Authorship Correction: Application of the Total Productive Maintenance to Increase the Overall Value of Equipment Effectiveness on Ventilator - Herry Agung Prabowo; Indra Maulana Fahturizal; Hibarkah Kurnia (Jurnal Optimasi Sistem Industri, 2024)
A ventilator machine is a medical device that plays an important role in handling Covid-19 cases during a pandemic. Covid 19 patients are arriving at a referral hospital in Jakarta, meaning that the hospital must prepare its medical equipment, including a ventilator machine. The ventilator machine experienced problems because the efficiency of the machine decreased so many patients waited in the ICU room. Machine effectiveness has an average value of 62.26% so it has an impact on disrupting patient services at home. The purpose of this research is to look for factors that cause the lack of effective value of ventilator machines and find effective solutions to increase the effectiveness of ventilator machines so that they can serve Covid-19 patients during a pandemic. This research method combines Focus Group Discussion in determining 5W+1H and implementing the pillars of Total Productive Maintenance to improve the Overall Effectiveness of Equipment on Ventilator machines. This study found a breakdown factor of 54.10%, idle and minor loss of 41.20%, and others of 4.70%. The effect of overall improvement has been able to increase the average effectiveness value by 85.00% from Sep 2021-Feb 2022, so this is supported by the hospital's program in terms of increasing the effectiveness of machines in patient care.